Atrial fibrillation is associated with impaired left ventricular energetics that persist despite successful catheter ablation - Wijesurendra, R; Liu, AQ; Eichhorn, C; Ariga, R; Levelt, E; Clarke, WT; Rodgers, CT; Karamitsos, TD; Bashir, Y; Ginks, M; Rajappan, K; Betts, T; et al. (Oxford University Press, 2016)
Atrial fibrillation (AF) is associated with subclinical left ventricular (LV) dysfunction and overt heart failure, but causal relationships are incompletely defined. Both AF and LV dysfunction may be tissue-specific manifestations of an underlying subclinical cardiomyopathy.